KETERSEDIAAN SUMBER ZAT BESI, ZAT PEMACU DAN PENGHAMBAT ABSORPSI ZAT BESI DALAM HUBUNGANNYA DENGAN KADAR HB DAN DAYA TAHAN FISIK ATLET SENAM PERSANI JATENG - Agustin Syamsianah; Erma Handarsari (Universitas Muhammadiyah Semarang, 2008)
Levels of iron in the various body compartments – collectively knownas iron status – are the particular importance to the athlete. The iron function are producing haemoglobine, myoglobine, role in enzyme function, and the oxygen transport from the lung interface with the athmosphere to the muscle capillaries and subsequent delivery to the mitochondria within the muscle cells.The objective of this research is to analyze the availability of ironresources, the iron spur and inhibitors, correlation effects within haemoglobine level and endurance of gymnastics athletes of “PERSANI Jawa Tengah”.The research design is an explanatory research with cross sectionaldesign. The total of twenty three (23) athletes are selected as samples.There is no significant correlation between the iron resources withhaemoglobine level (p = 0, 708 ) and so between the iron resources withendurance (p = 0, 872 ). There is a significant correlation between the ironcomsumption with haemoglobine level (p = 0, 000). But there is no significant correlation between the iron consumption with endurance (p = 0, 591).There is a significant correlation between the iron spur with haemoglobine level (p = 0, 000). But there is no significant correlation betweenthe iron spur with endurace (p = 0, 971).There is a negatif significant correlation between the iron inhibitorswith haemoglobine level (p = 0, 033 ; r = -0,446) but no significant correlation between the iron inhibitors with endurance (p = 0, 638).This result suggested that the iron consumption and the iron spur areable to increase the haemoglobine level but no for endurance. But the ironinhibitors is able to decrease the haemoglobine level but no for endurance. The iron spurKey Words : iron resources, iron spur, iron inhibitors, haemoglobine levels,endurance